Restructuring Spiritualism in New Life: Conversion to Christianity in Pokhara, Nepal - Upadhyay, Prakash (Janapriya Journal of Interdisciplinary Studies, 2020)
Christianity entered Nepal more than three and half centuries ago but religious conversion is still a contentious issue. This paper explores the trend of conversion to Christianity in Pokhara, Nepal. The study method was qualitative and quantitative. Observation, interview schedule and case study guidelines were used to obtain data from 70 converts of AG Church, Fulbari, Pokhara. The study findings reveal that females and oppressed of all caste/ethnicities with low occupational status were more interested in conversion. With no single cause of conversion, process and consequence, there is a nexus between conversion and modernity, consequences and the elements of continuity. With healing and church charity as the key motivations behind conversion, people convert with different intentions to overcome health problems, discontent with present religion, for money, friends and family influences. Christian church activates charities/supports for conversion. Conversion as a choice is a product of modern individualism, and the converts perceived contentment and changes in post-convert life. The accusation that conversion to Christianity is for financial gains may be valid for those who come with expectations, but the majority converts economic status is not satisfactory. In the absence of a state sponsored health and social security system, prevailing socioeconomic inequalities and pseudo-scientific non-medics superstition of church, conversion may be a way to break predominant sociocultural hierarchy/barriers. Hence, it should not be very surprising that many more will adopt Christianity in future. Educational systems should be reformed to reflect each religion’s genuine teaching and ideology and hence generate awareness on proselytizing.